PERSEPSI PENGGUNA MODA TRANSPORTASI TERHADAP PENGGUNAAN BAHASA DI RUANG PUBLIK DI SEMBILAN KOTA INDONESIA - Amran Purba (Balai Bahasa Sumatera Utara, 2019)
This study aims to determine the perceptions of users of transportation modes on language use at airports, stations, terminals, and ports in nine cities in Indonesia and to find out how far the application of language usage rules is applied to transportation modes. The method used in this study is a quantitative and descriptive qualitative approach. The research data is carried out by primary data collection in the field, namely the perception (view) of the users of transportation modes at airports, stations, terminals, and ports. The results of the study show that there are six cities (still dominant) agreeing on the use of Indonesian in the modes of air, sea, land and rail transportation. Then, there are two cities that even strongly agree on the use of Indonesian in the mode of transportation. Furthermore, there is one city that states that it is not agreeable to use Indonesian. Thus, perceptions of language users in transportation modes predominantly have high weight values. So, users of the transportation mode still have the concern to maintain or prioritize the use of Indonesian instead of foreign languages. Meanwhile, regional languages can also be used as a third language in the area rather than in the capital city.